Comparison of two different matrix-based autologous chondrocyte transplantation systems: 1 year follow-up results - Flohe, Sascha; Russe, K.; Wild, M.; Windolf, J.; Schulz, M.; Betsch, Marcel (European Journal of Trauma and Emergency Surgery, 2011)
Purpose: The treatment of full-thickness cartilage defects of the knee is a common problem in orthopaedic surgery. Autologous chondrocyte transplantation (ACT) is one of the few reliable treatment options of cartilage defects with good long-term outcomes. The improvement of ACT led to the matrix-based ACT (MACT). The purpose of the study was to compare two different commercially available MACT systems. Methods: Eleven patients with a cartilage defect of the knee were treated with the MACI® system and another nine patients with the CaRes® implant. The patients were prospectively followed and re-examined after one year. Results: One year after surgery all but one patient have significantly improved in their clinical outcome. Both types of MACT revealed similar results in terms of increase in level of activity, pain relief and knee function. Conclusion: The study showed that MACT is a good therapeutic option for full-size defects of the femoral condyle. The MACI® implant seems to be easier to handle which is reflected by smaller incisions and a shorter operation time. © 2010 Urban & Vogel.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Arthroscopy; Autologous chondrocyte transplantation; Cartilage defect; Chondrocytes; Matrix-based autologous chondrocyte transplantation